A Cross-Sectiona Study on Health Risk Behaviours Among Adolescents in Urban Coimbatore, India - Abinaya Dhandapani; P. Rathan; G. Sugunadevi (Universitas Airlangga, 2026)
There are over 1.2 billion adolescents globally. In India, adolescents make up 21.8% (i.e.,. 250 million) of the population. In the South East Asia Region (SEAR), there are about 360 million adolescents, comprising around 20% of the population. Adolescents are the backbone of the growing world, becoming the future economy and labor force. Without a healthy transition, they may lead unproductive lives. Investing in adolescent health and welfare is crucial for global development. To identify health-risk behaviors and assess the factors influencing them among adolescentsaged14-17yearsin an urban field practice area of Coimbatore. A cross-sectional study was conducted from June 2021 to May 2022 using the WHO-designed Global School-Based Health Survey (GSHS) questionnaire. A two-stage sampling method selected 420 participants. Fruit and vegetable consumption was low (1.4% and 5%), while intake of carbonated and sugar-sweetened drinks was high (70% and 62%). About 21.4% were high-risk smokers (smoked >10 days), and 60% had at least one alcoholic drink in the past 30 days. Although 75.2% were physically active and 83.1% did muscle-strengthening exercises, 84.8% rode bicycles fewer than three days a week, indicating a high risk of physical inactivity. The results underscore the need for intervention programs to increase fruit and vegetable consumption and to integrate other risk factors, such as physical activity, into health promotion among adolescents. There is a need for awareness against the harmful effects of tobacco and alcohol.